Influencia de las captaciones y colocaciones en el rendimiento de la banca privada en Ecuador - Poma Morocho, Gabriela Cristina (2024)
Within the financial system is the private bank, which is a fundamental part of the Ecuadorian economy, since the role they play is that of financial intermediation, which is based on capturing deposits from the public and placing them through credit, unlike other financial entities, this one is distinguished by the search for profitability, since they are for-profit entities. For this reason, the research objective is to study the influence of deposits and placements on the performance of private banking in Ecuador. A mixed approach with a descriptive, longitudinal, and correlational nature was used, given that the evolution was characterized and analyzed. of private banks grouping them by asset size, the study variables were related through a correlational analysis, and management strategies were proposed. As results, it was obtained that the group of large and medium-sized banks are stable, small banks place more than they deposit, have a high delinquency rate and negative profitability, it was also obtained that there is a strong relationship between deposits and placements in private banks in general, large banks have a strong relationship between deposits, loans, and profitability, while small banks present an inversely proportional relationship. Based on the above, it was identified that the group of small banks show deficiencies, in such a way that strategies were proposed to improve their management regarding expense control, portfolio management and diversification of products and services.